The relationship between the prevalence of urinary incontinence and quality of life in university students - Şener, Nurdilan; Şolt, Ayça (Mersin University, 2022)
Objective: This study was conducted to investigate the relationship between urinary incontinence prevalence and quality of life in university students. Method: 487 university students participated in this descriptive and relation-seeking cross-sectional study. The research was collected online between the dates of 20.09.2021 and 20.11.2021 through google survey forms. Personal information form, Urinary Distress Inventory-6/UDI-6 and Incontinance Impact Questionnaire-7/ IQ-7 were used to collect data. Data were analyzed with SPSS 22 program using mean, standard deviation, percentile and Man Whitney U test. Significance value was accepted as p value less than 0.05. Results: The mean age of the students who participated in the study was 20.42±2.14. It was determined that 17.5% of the students had urinary incontinence, and 11.2% of the students got stuck in their urine while going to the toilet. When the relationship between incontinence and quality of life was evaluated, it was determined that the quality of life of the students with incontinence was statistically significantly lower than the students without incontinence (p<0.05). Conclusion: In the study, it was determined that urinary incontinence negatively affected the students' quality of life.

Amaç: Bu araştırma, üniversite öğrencilerinde üriner inkontinans prevalansı ile yaşam kalitesi arasındaki ilişkinin araştırılması amacıyla yapılmıştır. Yöntem: Tanımlayıcı ve ilişki arayıcı olan bu kesitsel araştırmaya 487 üniversite öğrencisi katılmıştır. Araştırma 20.09.2021-20.11.2021 tarihleri arasında google anket formlar aracılığıyla online olarak toplanmıştır. Verilerin toplanması için kişisel bilgi formu, Urogenital Distres Envanteri /UDI-6 (Urinary Distress Inventory-6) ve İnkontinans etki Anketi/ IQ-7 Formu (Incontinance Impact Questionnaire-7) kullanılmıştır. Veriler SPSS 22 programı ile ortalama, standart sapma, yüzdelik ve Man Whitney U testi kullanılarakanaliz edilmiştir. Anlamlılık değeri p değeri 0.05 den küçük olarak kabul edilmiştir. Bulgular: Çalışmaya katılan öğrencilerin yaş ortalaması 20.42±2.14’tür. Öğrencilerin %17.5’nin idrar kaçırdığı, %11.2’nin ise idrara sıkışıp tuvalete giderken idrar kaçırdığı saptanmıştır. İnkontinans ile yaşam kalitesi arasındaki ilişki değerlendirildiğinde ise, inkontinansı olan öğrencilerin yaşam kalitelerinin, inkontinansı olmayan öğrencilere göre istatistiksel olarak anlamlı şekilde düşük olduğu tespit edilmiştir (p<0.05). Sonuç: Araştırmada üriner inkontinansın, öğrencilerin yaşam kalitelerini olumsuz etkilediği belirlenmiştir.
Üniversite öğrencilerinde üriner inkontinanas prevalansı ile yaşam kalitesi arasındaki ilişki
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi